Beyond HRD status: Unraveling Genetic Variants Impacting PARP Inhibitor Sensitivity in Advanced Ovarian Cancer - Kjeldsen, Maj K.; Jørgensen, Morten; Grønseth, Dina Sofie B.; Schønemann-Lund, Martin; Nyvang, Gitte-Bettina; Haslund, Charlotte Aaquist; Knudsen, Anja Oer; Motavaf, Anne Krejbjerg; Malander, Susanne; Anttila, Maarit; Lindahl, Gabriel; Mäenpää, Johanna; et al. (American Association for Cancer Research (AACR), 2025)
The management of advanced ovarian cancer (AOC) has undergone significant advancements with the emergence of molecular diagnostics, particularly in predicting responses to poly(ADP-ribose) polymerase inhibitors (PARPi) based on homologous recombination deficiency (HRD) status. However, understanding sensitivity and resistance beyond HRD status remains elusive. This study aims to explore molecular factors that may elucidate why HRD status does not consistently predict PARPi sensitivity. Therefore, we conducted a post hoc translational analysis of formalin-fixed paraffin-embedded tumor samples from the ENGOT-ov24/NSGO-AVANOVA part 1 and 2 trial (AVANOVA1&2; NCT02354131), focusing on alterations pertaining radiological response and progression-free survival (PFS). DNA sequencing was performed using the TruSight Oncology 500 HT gene panel, with variants classified according to recent guidelines. HRD status had been assessed by Myriad MyChoice® CDx. We identified, among 92 patients in the AVANOVA1&2 trial, 151 pathogenic or likely pathogenic variants across 81 samples. PARPi sensitizing variants were found in two out of ten HRDneg samples from patients with clinical benefit (PFS ≥ 12 months), while three out of ten HRDpos samples from patients having no benefit (PFS ≤ 6 months) harbored variants associated with PARPi resistance. Additionally, analysis of BRCA1 variants revealed that truncating variants in exon 11 correlated with clinical benefit when niraparib was combined with bevacizumab. Conclusively, our findings highlight the complexity of PARPi response in AOC and underscore the importance of exploring somatic variants beyond HRD status. Further investigation into exon 11 variants of BRCA1 and the potential of combination treatment is warranted.